Humanistic Perspectives of Biocultural Diversity - Sadowski, Ryszard F. (Problemy Ekorozwoju, 2019)
It is widely recognised that biocultural diversity is an important element of world heritage. Until recently, the focus was mainly on biodiversity, but since the 1980s, attention has also been drawn to the importance of cultural and linguistic diversity. Konrad Lorenz suggests that civilisational processes are threatening not only the diversity of Earth’s heritage, but also humanity itself. This study aims at showing the interrelationships between biocultural diversity and the biological and cultural layers of humans. This study draws on Luisa Maffi’s concept of biocultural diversity and Lorenz’s layered concept of humans. The research conducted confirms the existence of mutual dependencies between various forms of terrestrial heritage and human layers. It also suggests that strong biocultural diversity positively affects the human condition and, vice versa, the good condition of humans positively affects the quality of the Earth’s diversity. The research leads to the conclusion that research teams analysing civilisational processes cannot be limited only to representatives of natural, technical, economic or legal sciences, but should also include humanists. This will allow a better understanding of the complexity characterising civilisational processes and find more adequate solutions.